GEOGRAPHICAL DISTRIBUTION OF PREVALENCE LEVELS DRUG USE IN POPULATION OF HIGH SCHOOL EDUCATION IN COSTA RICA, 2015 - Chacón Serrano, William (Revista Geográfica de América Central., 2017)
Drug use in high school population represents a line of research that has emerged more strongly in recent years in Costa Rica due to the increased consumption of drugs like alcohol and marijuana.Prevalence levels have changed considerably in the last 10 years. Since 2006, there have been efforts to monitor the consumption levels in this population; however, for the 2015 study, geographic variables that could represent the consumption indicators at province and region level were included to give a broader perspective of the phenomenon in the Costa Rican population. It was possible to show the differentiated behavior of prevalence levels of consumption in different provinces, thus opening the debate on the conditions by province regarding the phenomenon behavior.